Compactons of binary bose gases in optical lattices with inter-species scattering length management - Abdullaev, Fatkhulla; Abdul Hadi, Muhammad Salihi; Salerno, Mario; Umarov, Bakhram A. (OSA - The Optical Society, 2016)
Binary mixtures of quasi one-dimensional Bose-Einstein condensates (BEC) in deep optical lattices and in the presence of periodic rapid modulations of the interspecies scattering length are investigated. In the strong management limit the existence of binary compactons of stationary and quasi-stationary type is demonstrated. The existence of a threshold on the inter-species scattering length in the case of quasi-stationary compactons is shown.